2020
DOI: 10.1177/0959354320934182
|View full text |Cite
|
Sign up to set email alerts
|

Reflective function: A move to the level of concern

Abstract: Reflective function (RF) is the capacity to reflect on one’s own thinking and feelings, as well as on that of others. It involves an increasingly complex awareness that there is more than what is visible on the surface. Most studies of RF have focused on its significance for self-development and interpersonal relationships in dyadic and family contexts. In this article, I suggest that by imparting a more accurate perception of the intra- and interpersonal reality and interrelatedness, RF is inextricably relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Perhaps interventions to promote RF are needed for those in power-for the factory owners and managers-to assist them to hold their employees in mind regarding their work conditions and policies for returning mothers. Unsupportive social systems need to be interrogated and challenged through advocacy work, employing mentalization-based interventions to widen our circles of concern (Benbassat, 2020). Specifically, putting energies into creating a ''cultural context in which it is reasonable to expect to have one's thoughts and feelings taken into account'' (Campbell & Allison, 2022, p. 208).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps interventions to promote RF are needed for those in power-for the factory owners and managers-to assist them to hold their employees in mind regarding their work conditions and policies for returning mothers. Unsupportive social systems need to be interrogated and challenged through advocacy work, employing mentalization-based interventions to widen our circles of concern (Benbassat, 2020). Specifically, putting energies into creating a ''cultural context in which it is reasonable to expect to have one's thoughts and feelings taken into account'' (Campbell & Allison, 2022, p. 208).…”
Section: Discussionmentioning
confidence: 99%
“…Connolly (2003), in this context, succinctly links the inability to tolerate differences with the experience of terror and tyranny. Benbassat (2020) notes that insufficient development of mentalization is closely related to the tendency to unethical, domineering behaviour, while the predictor of ethical and moral behaviour is well‐developed mentalization.…”
Section: Mentalization Of War‐induced Trauma and Totalitarian State O...mentioning
confidence: 99%
“…A longitudinal path analysis in Canada (n = 385) found that maternal cognitive sensitivity (e.g., parental ability to cognitively stimulate their child) mediated the association between maternal RF (referred to as maternal 10.3389/fpsyg.2022.995426 reflective capacity), measured when children were 18 months old, and 4-year-old children's executive functioning, theory of mind, and receptive language (Wade et al, 2018). Studies have also reported that maternal RF is positively associated with school-aged children's RF (Ensink et al, 2015;Rosso and Airaldi, 2016), and as RF demands cognitive abilities, such as perceiving and processing mental states and emotions (Slade, 2005;Benbassat, 2020), the results of these studies support a link between maternal RF and children's cognitive abilities.…”
Section: Parental Reflective Function and Children's Cognitive Abilitiesmentioning
confidence: 99%